KETRAMPILAN KREATIF DIFABILITAS DAN HAK-HAK BELAJAR ANAK PASCA PANDEMIC-COVID 19 KAJIAN PAK PEMBEBASAN - Lourine S Joseph (TANGKOLEH PUTAI, 2022)
This article is the result of a christian religius education study on the release of creative sills and learning rights for children with disabilities after the covid 19 pandemi in the Kusu-Kusu Sereh hamlet. This article seeks to explore the difficulties of developingthe potential and creativity of children with desabilities doe to the low attention and commitmen of parents and the discriminatory government. This article collects data through recorded interviews, and the discussion with 50 respondent in several families in the village of urimessing,hamlet kusu-kusu sereh as well as analysisof instrument items obtained from the result of distribution to respondent. The result of the study indicate that difficult of people with disabilities developing their potential and creativity is due to the low attention of famillies and the goverment in the fullfilling the rights of people with disabilities. Family attention and goverment policies are limited to normal children. Therfore, futher research must be more comprehensive in integrating the views of parents and the goverment as well as other education observers to pay attention to the rights of marginalized person with disabilities through the christian religius education liberation study.